plzz help and explain step by step
Attachments:
![](https://hi-static.z-dn.net/files/d2d/13e2179db3142d5e2ab4b3a994f18ce7.jpg)
Answers
Answered by
0
Explanation
Let x³ = a then,
f(a) = a² -7a -8
f(a) = a² - 8a + a -8
f(a) = (a-8 ) ( a+1)
here , f(a) = 0
therefore ,
=> a-8 = 0
=> a = 8
=> a = 8 = x³
so , x = 2
Answered by
8
Answer:
your ans
Step-by-step explanation:
pls follow me❤
always be happy..❤❤
mark as brainlist❤❤❤❤
be happy❤❤❤❤
Attachments:
![](https://hi-static.z-dn.net/files/db5/331b4f1b0307e52b63d2753bb5e2af39.jpg)
![](https://hi-static.z-dn.net/files/d5d/36a5702a835dbd5c77c3fccccc883801.jpg)
Similar questions
CBSE BOARD X,
6 months ago
Environmental Sciences,
6 months ago
Math,
1 year ago
History,
1 year ago
Math,
1 year ago
Biology,
1 year ago